Risk Factors for HIV Transmission Among Hispanic Men Who Have Sex With Men in Atlanta - Valerie Hepburn; Denyse Nanan (Georgia Southern University, 2007)
This study assessed and compared demographic factors, psychosocial factors, health seeking behavior, and sexual practices of two convenience samples of Hispanic/Latino gay men and men who have sex with men (MSM) in the metropolitan Atlanta region. The aim was to obtain data on emerging HIV/AIDS patterns in this group. Bilingual surveys were conducted in 2000 and 2006 at local gay bars. Discrepancies observed between HIV/AIDS knowledge and sexual behaviors in 2000 were replicated in 2006. Contrary to expected improvements due to enhanced HIV/AIDS education and awareness, risk behavior for HIV/STDs increased significantly between 2000 and 2006. These findings should inform the design and delivery of programs aimed at meeting the HIV/AIDS prevention, education and treatment needs of this growing population.